Ethics and policies for cyber operations a NATO Cooperative Cyber Defence Centre of Excellence initiative - Glorioso, Ludovica; Taddeo, Mariarosaria (Philosophical studies series, 2017)
This book presents 12 essays that focus on the analysis of the problems prompted by cyber operations (COs). It clarifies and discusses the ethical and regulatory problems raised by the deployment of cyber capabilities by a state's army to inflict disruption or damage to an adversary's targets in or through cyberspace.